Impact of Navigated Task-specific fMRI on Direct Cortical Stimulation - Leote, Joao; Loução, Ricardo; Viegas, Catarina; Lauterbach, Martin; Perez-Hick, António; Monteiro, Joana; Nunes, Rita G.; Ferreira, Hugo A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aims Cortical mapping (CM) with direct cortical stimulation (DCS) in awake craniotomy is used to preserve cognitive functions such as language. Nevertheless, patient collaboration during this procedure is influenced by previous neurological symptoms and growing discomfort with DCS duration. Our study aimed to evaluate the impact of navigated task-specific functional magnetic resonance imaging (nfMRI) on the practical aspects of DCS.Material and Methods We recruited glioma patients scheduled for awake craniotomy for prior fMRI-based CM, acquired during motor and language tasks (i.e., verb generation, semantic and syntactic decision tasks). Language data was combined to generate a probabilistic map indicating brain regions activated with more than one paradigm. Presurgical neurophysiological language tests (i.e., verb generation, picture naming, and semantic tasks) were also performed. We considered for subsequent study only the patients with a minimum rate of correct responses of 50% in all tests. These patients were then randomized to perform intraoperative language CM either using the multimodal approach (mCM), using nfMRI and DCS combined, or electrical CM (eCM), with DCS alone. DCS was done while the patient performed picture naming and nonverbal semantic decision tasks. Methodological features such as DCS duration, number of stimuli, total delivered stimulus duration per task, and frequency of seizures were analyzed and compared between groups. The correspondence between positive responses obtained with DCS and nfMRI was also evaluated.Results Twenty-one surgeries were included, thirteen of which using mCM (i.e., test group). Patients with lower presurgical neuropsychological performance (correct response rate between 50 and 80% in language tests) showed a decreased DCS duration in comparison with the control group. None of the compared methodological features showed differences between groups. Correspondence between DCS and nfMRI was 100/84% in the identification of the precentral gyrus for motor function/opercular frontal inferior gyrus for language function, respectively.Conclusion Navigated fMRI data did not influence DCS in practice. Presurgical language disturbances limited the applicability of DCS mapping in awake surgery.
Keywords: glioma; awake surgery; navigated functional magnetic resonance imaging; direct cortical stimulation